Evaluasi Penggunaan Aplikasi Coretax untuk Meningkatkan Kepatuhan Pajak dan Akuntabilitas Pengelolaan Pajak pada Rumah Sakit Angkatan Laut (RUMKITAL) Dr. Mintohardjo - Linsanyu Linsanyu; Faurna Lusiani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to evaluate the use of the CoreTax application in improving tax compliance and the accountability of tax management at the Navy Hospital (Rumkital) dr. Mintohardjo. The research adopts a qualitative approach with descriptive analysis, gathering data through interviews, observations, and document studies. The findings indicate that the implementation of the CoreTax application has significantly contributed to improving tax compliance and more transparent tax administration management. The use of this application facilitates the timely reporting and payment of taxes, as well as enhancing accountability in tax management. However, there are still challenges related to the limitations in human resources and user training, which need to be addressed to optimize the benefits of this application. This study recommends that Rumkital enhance the capacity of human resources in using the application and conduct regular evaluations of the tax management process.